EKSPLORASI PERAN MAHASISWA PGSD DALAM MENINGKATKAN LITERASI DAN NUMERASI DI SEKOLAH DASAR - Ulin Husnul Khotimah; Silvina Noviyanti (STKIP Subang, 2025)
This research aims to explore the strategic role of students from the Primary School Teacher Education Study Program (PGSD) in improving students' literacy and numeracy skills at the elementary school level. The urgency of this research is based on Indonesia's low ranking in the 2022 PISA survey, where literacy scores in reading (355 points) and mathematics (379 points) are far below the international average. Apart from that, the results of observations at SDN 13/I Muara Bulian show low interest in independent reading, dependence on teacher instructions, and students' fear of mathematics which is considered a